How to measure fatigue among pilots? - Jerman, Andrej (Array, 2018)
Fatigue represents a major problem in aviation. Therefore, it is important to identify fatigue among pilots early enough before an incident or an accident occurs. The aim of our study has been to conduct a literature review on measurements of fatigue among pilots; to find out which measurements are used to recognize fatigue and what the results of conducted studies are with the focus on the usefulness of tests for measuring fatigue. The findings are based on meta-analysis. For the purpose of our study, we have used electronic databases Google Scholar, Emerald, MedLit and Academic Search Complete. The content analysis of the articles has been used to summarize and compare qualitative data. The results obtained show that tests for measuring fatigue can be divided into two groups, objective tests and subjective tests. Pilots’ subjective fatigue is mostly evaluated using Samn-Perelli fatigue scale, which is widely used in the aviation industry and it provides data for comparison. The contribution of our study is the widened understanding of fatigue measuring and usefulness of these measurements among pilots. The findings of our research are descriptive in nature. Further studies should be focused on deeper investigation of this topic and could include case studies of fatigue among pilots with qualitative data.